Strategi Visual Animasi 2d Sebagai Media Edukasi Aksi Bersih Di Sungai Ciliwung - Celine Hermawan (VisArt: Jurnal Seni Rupa dan Design, 2025)
The Ciliwung River is a major waterway in Jakarta that has been heavily polluted due to indiscriminate waste disposal. This pollution damages ecosystems, triggers flooding, and reduces the quality of life of surrounding communities. The recurring pollution of the Ciliwung River indicates that technical mitigation efforts alone are insufficient without the development of environmental awareness from an early age. Children, as the next generation, play a strategic role in fostering sustainable pro-environmental behavior. The urgency of this research lies in the need for effective, communicative, and child-appropriate visual educational media, so that messages about river conservation can be received, understood, and applied in daily life. This study aims to design an educational 2D animation for children aged 8–12 years to increase awareness of the importance of maintaining river cleanliness. A qualitative approach is employed through interviews with World Cleanup Day Indonesia and residents living around the Ciliwung River, as well as a literature review on pollution and river cleanup efforts. The results will be developed into an animation featuring emotional storytelling, engaging visuals, and easily understood messages to encourage children to stop littering in rivers and actively participate in keeping them clean. It is expected that this animation will serve as an impactful educational medium for the environment and society.